Substituting for the State: The Role of Volunteers in Defense Reform in Post-Euromaidan Ukraine - Zarembo, Kateryna (Kyiv-Mohyla Law and Politics Journal, 2017)
While the role of volunteers in sustaining the Ukrainian armed forces against the backdrop of Russian aggression since 2014 has been widely acknowledged in literature, the effect of volunteer initiatives on the state defense capacity in longer term has not been studied thus far. This article aims to address this gap and explore whether volunteer participation led to institutional strengthening of the Ukrainian defense state capacity or to its weakening. The analysis will conclude that the volunteers in fact contributed to both – strengthening the state and weakening it at the same time; the outcome dependent on the context in which the volunteers took action at different times. While volunteer participation failed to bring about systemic reform, it did provide powerful democratic oversight over the state’s key defense institution.